Smart cities and citizen engagement: Evidence from Twitter data analysis on Italian municipalities - Silvia Blasi; E. Gobbo; Silvia Rita Sedita (Journal of Urban Management, 2022)
Smart cities are increasingly keen to establish a fruitful conversation with their citizens, to better capture their needs, and create virtual platforms for stimulating co-creation processes between government and users, with the final objective of increasing the quality of life and well-being. Social media applications provide an opportunity for dialogic communication, where, for a relatively low cost, a large amount of information reaching a wide audience can be published and exchanged in real time, fueling opportunities for citizens' engagement. This study is based on a social media listening method, through Twitter data mining, which enabled disentangling different components of citizen engagement (popularity, commitment, and virality) for a sample of Italian municipalities. In addition, we executed a deep analysis of the types of communication artifacts exchanged and, through a content analysis of the tweets published by followers of the municipalities' accounts, we identified the main areas of interest in the social media conversations. Our results are based on the analysis of online conversations engaged by followers of Twitter accounts of a sample of 28 Italian municipalities, chosen among the most active and densely populated. We show that municipalities tend to use the Twitter account as a channel of communication to inform the population about a variety of topics, such as transport and public works, among the others. The volume of activity and number of followers (audience) vary from one municipality to the other. There is generally a negative relationship between the density of the population of a municipality and citizens' engagement: smaller municipalities show a higher citizens' engagement; the biggest ones, like Roma, Milan, Turin, Naples, are laggards. We finally conducted a city profiling process, which provides a representation of key citizens' segments in terms of engagement. Policymakers could find in our work useful tools to increase citizens' listening capacity.
Keywords: 710; Smart citiese-Government; Twitter; Web scraping; Social media listening; We-government